2020
DOI: 10.3390/ijms21030968
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin 1 Is Involved in Neuropathic Pain and Electroacupuncture-Mediated Analgesic Effect

Abstract: Numerous studies have verified that electroacupuncture (EA) can relieve neuropathic pain through a variety of mechanisms. Synaptotagmin 1 (Syt-1), a synaptic vesicle protein for regulating exocytosis of neurotransmitters, was found to be affected by EA stimulation. However, the roles of Syt-1 in neuropathic pain and EA-induced analgesic effect remain unclear. Here, the effect of Syt-1 on nociception was assessed through an antibody blockade, siRNA silencing, and lentivirus-mediated overexpression of spinal Syt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Although peripheral nerves have a reconstitutive ability, it is difficult to fully recover nerve function after PNI. EA is not only effective in treating PNI [ 53 ] but can also be used for the treatment of neuropathic pain [ 54 ] and central nervous disease [ 55 ]. Since miRNAs are closely associated with the development of PNI [ 15 , 32 , 33 , 41 , 56 59 ] and nerve repair, while exosomes are valuable carriers of miRNAs [ 60 ], our study focused on exosomal delivery of miR-21 to explore the effects of EA.…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral nerves have a reconstitutive ability, it is difficult to fully recover nerve function after PNI. EA is not only effective in treating PNI [ 53 ] but can also be used for the treatment of neuropathic pain [ 54 ] and central nervous disease [ 55 ]. Since miRNAs are closely associated with the development of PNI [ 15 , 32 , 33 , 41 , 56 59 ] and nerve repair, while exosomes are valuable carriers of miRNAs [ 60 ], our study focused on exosomal delivery of miR-21 to explore the effects of EA.…”
Section: Discussionmentioning
confidence: 99%
“…15 The expression of synaptotagmin 1, a synapse-related protein, increased in rats with nerve injury, while EA decreased its expression and induced better behavioural performance. 24 Studies have also shown that the application of EA can inhibit the LTP of synaptic transmission of rats with hyperalgesia in the hind limbs. 16 The data in our study showed that the thermal and mechanical nociceptive thresholds could be increased after EA at ST36 and BL60 in the M + EA group compared with the M group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, drugs used to relieve neuropathic pain, including opioids and tricyclic antidepressants, do not meet the clinical needs and commonly induce drug resistance [ 3 , 27 ]. EA, a simple and efficacious treatment method that is usually used to improve neuropathic pain, has long been the focus of researchers [ 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%